Forest plantations how primary source for fuel cells. - Gomes, Sérgio Inácio; Jorge, Luiz Mário Matos; Ravagnani, Mauro Antônio Silva Sá; Paraíso, Paulo Roberto; Conceição, Wagner André Santos; Andrade, Cid Marcos Gonçalves (Revista Ciências Exatas, 2009)
The sources of petroleum and other fossil fuels will be exhausted in the coming decades and/ or tend to have their costs too high and must be restricted to certain uses. Moreover, global warming requires urgent changes in energy policies, looking for primary renewable sources with and low impact, negative, on the environment. This work studied the feasibility of the use of forest plantations for the production of primary energy to be used in fuel cells. Fuel cells can be regarded as an energy accumulator, with the advantage of being highly efficient and clean. In this work is presented the principles of mathematical modeling used for the simulation of relations between the basic factors of productivity of forest plantations with the generation of power through hydroelectric, and the balance of carbon. The aim was to establish relationships between many variables when considering the importance of these relations as regards the concern about the social and environmental aspects. The forest plantations were showed as a viable alternative as a primary energy source for fuel cells, especially taking into account the environmental and social factors.